Chew Wi Kang recipient of Perodua Excellence Award - UMP, PNC (2019)
"To succeed, we need to focus and believe in ourselves. There is always obstacles in our path, but we need to go extra mile to achieve what we dream for,” said Chew Wi Kang, the recipient for Perodua Excellence Award at the Universiti Malaysia Pahang (UMP) 14th Convocation Ceremony.